Nonactivated and Activated Biochar Derived from Bananas as Alternative Cathode Catalyst in Microbial Fuel Cells. (26th August 2014) - Yuan, Haoran; Deng, Lifang; Qi, Yujie; Kobayashi, Noriyuki; Tang, Jiahuan
Abstract : Nonactivated and activated biochars have been successfully prepared by bananas at different thermotreatment temperatures. The activated biochar generated at 900°C (Biochar-act900) exhibited improved oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) performances in alkaline media, in terms of the onset potential and generated current density. Rotating disk electron result shows that the average of 2.65 electrons per oxygen molecule was transferred during ORR of Biochar-act900. The highest power density of 528.2 mW/m 2 and the maximum stable voltage of 0.47 V were obtained by employing Biochar-act900 as cathode catalyst, which is comparable to the Pt/C cathode. Owning to these advantages, it is expected that the banana-derived biochar cathode can find application in microbial fuel cell systems.